The Impact of a Clinical Pharmacist in an Interdisciplinary Weight Loss Service: A Follow-Up Study - Beverly R. Francis; Laura Challen (University of Minnesota Libraries Publishing, 2021)
Background: At an Internal Medicine outpatient clinic, patients are referred to a weight loss service by their primary care physician to be managed by a clinical pharmacist and dietician. Objective: A study was conducted to determine the impact of this established, interdisciplinary, pharmacist-driven weight loss service on percent weight loss from baseline in patients who are obese or overweight compared to those receiving standard weight loss care. Methods: This was a retrospective, single-center, cohort study including adults ≥18 years of age with BMI ≥30 or BMI ≥27 with at least one weight-related comorbidity such as hypertension, dyslipidemia, or type 2 diabetes mellitus, and referred to the clinic's weight loss service or managed by their primary care physician. The primary outcome was percent weight loss from baseline. Key secondary outcomes included number of patients who had >5% weight loss in 6 months, number of patients who received liraglutide after 6 months, and percent weight loss in patients prescribed liraglutide. Statistical analysis included descriptive statistics, t-test for continuous outcomes, and chi-square test for between-group differences. Results: A total of 86 patients met inclusion criteria with 43 patients in the weight loss service group (intervention) and 43 patients in the primary care group (standard care). The intervention group had a significantly higher baseline weight and BMI than the standard care group (120.44 kg vs. 95.72 kg, p <0.001 and 45.34 kg/m2 vs. 37.62 kg/m2, p <0.001 respectively). The percent change in weight from baseline in the intervention group was a decrease of 3% compared to a decrease of 0.35% in the standard care group (p=0.03). Conclusions: Involvement of clinical pharmacist in interdisciplinary weight loss management through pharmacotherapy and other medication related services, shows considerable improvement in weight loss, when compared to the standard care of weight management. However, prospective randomized studies are warranted to further assess the benefits of a pharmacist-driven, interdisciplinary weight loss service.